The Care of the Successors in the Jurisprudential Schools: “The Jurisprudence of the Successor Kharijah ibn Zaid ibn Thabit al-Ansari” as a Model - Khadija Rajab Shahban (Journal of Scientific and Human Dimensions, 2026)
The research addresses the emergence of jurisprudential schools in the era of the Companions (may Allah be pleased with them) and the impact of the Islamic conquests on their dispersion across various regions. This contributed to the emergence of multiple jurisprudential schools distinguished by independent reasoning (Ijtihad), diverse methodologies of evidence-based deduction, and differing opinions according to the evidence. The research then highlights the role of the Successors (Tabi’in) in receiving these schools, consolidating their methodologies, and developing them further. The research focuses on Kharijah ibn Zaid ibn Thabit al-Ansari (may Allah have mercy on him) as one of the most prominent jurists of Medina during the era of the Successors. It does so by explaining his dedication to the jurisprudence of the Companions and analyzing his jurisprudential opinions and his inductive methodology for deriving legal rulings. The research aims to highlight his contribution to the development of Medinan jurisprudence and to demonstrate the influence of the early jurisprudential schools in shaping the science of Islamic jurisprudence.